Bosnia and Herzegovina : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses key findings of the Financial System Stability Assessment on Bosnia and Herzegovina (BiH). Economic and financial activity in BiH remains stuck in a low gear since the global financial crisis, reflecting weak external demand, tighter funding conditions, and deep-seated structural issues. Aggregate solvency and liquidity indicators appear broadly sound, but significant pockets of vulnerability exist. The banking system is more than 80 percent foreign-owned banks. The average regulatory capital adequacy ratio exceeded 16 percent as of end 2014. Decisive and timely actions to deal with weak banks are critical for preserving financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet